Cytokine alterations during paraneoplastic neutrophilia and leukemoid reaction in patients with advanced melanoma - Zhang, Xin-Wen; Wald, Alexander; Salzmann, Martin; Halama, Niels; Hassel, Jessica C. (Cancer immunology immunotherapy, 2023)
Paraneoplastic leukemoid reaction (PLR) is a rare phenomenon in metastasized melanoma associated with poor prognosis and rapid disease progression. Currently, no specific therapeutic options exist other than treating the underlying malignancy.